Changes in bronchial responsiveness to inhaled histamine over four years in middle aged male smokers and ex-smokers. Issue 8 (August 1988) - Lim, T K; Taylor, R G; Watson, A; Joyce, H; Pride, N B
Abstract : Bronchial hyperresponsiveness to inhaled histamine in smokers is associated with an accelerated annual decline in FEV1 and low baseline FEV1 values. The evolution of bronchial hyperresponsiveness and whether it precedes or follows the accelerated decline in FEV1 and reduction in FEV1 is unknown. Measurements of the provocative concentration of inhaled histamine required to reduce FEV1 by 20% (PC20) were repeated after a four year interval in 27 male smokers (mean age 59 years, smoking on average 27 cigarettes a day in 1986) and 16 men who were ex-smokers in 1982 and who remained non-smokers until 1986 (mean age 53 years in 1986). These men were originally recruited to a prospective study in 1974 and had their first PC20 measurement in 1982. PC20 was positively related to baseline FEV1 in both smokers and ex-smokers in both 1982 and 1986 (r ranging from 0.56 to 0.76, p less than 0.01). In smokers mean FEV1 fell from 83% to 77% predicted (p less than 0.001) and geometric mean PC20 from 7.11 to 3.27 mg/ml (p less than 0.001) between 1982 and 1986. The change in PC20 in individual smokers over the four years was related to change in FEV1 (p = 0.012). In ex-smokers mean FEV1 was 93% predicted both in 1982 and in 1986 and there was no significant difference in geometric mean PC20 between 1982 (6.68 mg/ml) and 1986 (5.98 mg/ml). Thus in smokers there was an accelerated annual decline in FEV1 and an increase in bronchial hyperresponsiveness as FEV1 fell. The ex-smokers had comparable levels of bronchial hyperresponsiveness in 1982. Mean PC20 values were unchanged in 1986 in these men, who showed a normal age related decline in FEV1. These longitudinal results emphasise the importance of baseline airway geometry in influencing bronchial hyperresponsiveness to histamine in middle aged smokers and ex-smokers.